Estrategia de comunicación integral para posicionar la imagen institucional del GADM del cantón Valencia - Gutiérrez Burgos, Tatiana Carolina (2022)
The purpose of this research work is to analyze the comprehensive communication for the positioning of the corporate image in the municipal GAD of the Valencia canton, which is based on theorists of the comprehensive communication and corporate image variables. The research is framed in the descriptive, applied modality, with a non-experimental, transactional, field design, to which the alternative answer questionnaire questionnaire interview instrument was applied. In the analysis, the result was observed, that government institutions plan communication strategies in general, they also use resources consciously, however, they do not plan communication at different levels, nor do they use communication resources in their entirety. On the other hand, it can be inferred that they moderately apply multidirectional ordering as an integrating mechanism. Therefore, the application of the recommendations proposed in this study is suggested.